từ hpt \Rightarrow x^{3}+ y^{3}+ z^{3} =x^{2} +y^{2}+z^{2} (*) từ pt (1) \Rightarrow x^{2}\leq1; y^{2}\leq 1; z^{2}\leq1 \Rightarrow -1\leq x,y,z\leq 1 +) 0\leq x,y,z \leq 1$\Rightarrow \sum_ x^{2}(x-1)\leq 0 (*)\Leftrightarrow \begin{cases}x=0, x=1 \\ y=0 ,y=1 \end{cases}và z=0 ,z=1.$ +) -1\leq x,y,z \leq0 TT như trên nhưng ta lại vì k tm ĐKVậy (x;y;z)= (0;0;1);(0;1;0);(1;0;0)
từ hpt \Rightarrow x^{3}+ y^{3}+ z^{3} =x^{2} +y^{2}+z^{2} (*) từ pt (1) \Rightarrow x^{2}\leq1; y^{2}\leq 1; z^{2}\leq1 \Rightarrow -1\leq x,y,z\leq 1 +) 0\leq x,y,z \leq 1\Rightarrow \sum x^{2}(x-1)\leq 0 (*)$\Leftrightarrow \begin{cases}x= 0;x=1\\ y= 0;y=1\end{cases}$và z=0 ,z=1. +) -1\leq x,y,z \leq0 TT như trên nhưng ta lại vì k tm ĐKVậy (x;y;z)= (0;0;1);(0;1;0);(1;0;0)